2018
DOI: 10.1177/2396941518761239
|View full text |Cite
|
Sign up to set email alerts
|

Successful passive sentence comprehension among Danish adolescents with autism spectrum disorders

Abstract: Background and aims: Language abilities vary greatly across children with autism spectrum disorders (ASD). In the present study, we investigate passive sentence comprehension, which has been underexplored among individuals with autism spectrum disorders and found to be delayed among other clinical populations. This study is the first to assess grammatical comprehension among Danish-speaking adolescents with autism spectrum disorders. Methods: Fifteen Danish-speaking adolescents with autism (mean age: 14.9 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(1 citation statement)
references
References 53 publications
(87 reference statements)
0
1
0
Order By: Relevance
“…Specifically, the results on syntactic awareness of sentences including articles revealed that ASD_LOW performed below children with SLI_HIGH, but not different from children ASD_HIGH. We also found that Raven scores contributed to explain the variance in ASD children' sensitivity to articles (see also Jensen de López et al, 2018 for the contribution from nonverbal IQ on language abilities). ASD children with low IQ performed worse than ASD children with normal IQ (the IQ effect disappeared when ASD children with low IQ were removed from the analysis).…”
Section: Discussionmentioning
confidence: 58%
“…Specifically, the results on syntactic awareness of sentences including articles revealed that ASD_LOW performed below children with SLI_HIGH, but not different from children ASD_HIGH. We also found that Raven scores contributed to explain the variance in ASD children' sensitivity to articles (see also Jensen de López et al, 2018 for the contribution from nonverbal IQ on language abilities). ASD children with low IQ performed worse than ASD children with normal IQ (the IQ effect disappeared when ASD children with low IQ were removed from the analysis).…”
Section: Discussionmentioning
confidence: 58%